2010
DOI: 10.1111/j.1540-8183.2010.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Changes of Fractional Flow Reserve in DK (Double Kissing), Crush, and 1‐Stent Technique for True Bifurcation Lesions

Abstract: In the acute phase, immediately after PCI for bifurcation lesion, DK crush stenting was associated with higher FFR and lower residual diameter stenosis in the SB, as compared with the provisional 1-stent group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…In a study by Lee et al ,[45] SB FFR was measured before and after kissing balloon dilatation in patients treated with the crush technique, and kissing balloon dilatation increased FFR from 0.94 ± 0.04 to 0.97 ± 0.03 ( P = 0.011). Another study reported that double kissing crush stenting was associated with higher SB FFR as compared with the provisional strategy in true bifurcation lesions (0.94 ± 0.3 in crush vs. 0.90 ± 0.08 in provisional group, P = 0.028) [46]. These results suggest that SB FFR can be helpful to assess the procedural success after SB stenting.…”
Section: Ffr After Sb Stentingmentioning
confidence: 84%
“…In a study by Lee et al ,[45] SB FFR was measured before and after kissing balloon dilatation in patients treated with the crush technique, and kissing balloon dilatation increased FFR from 0.94 ± 0.04 to 0.97 ± 0.03 ( P = 0.011). Another study reported that double kissing crush stenting was associated with higher SB FFR as compared with the provisional strategy in true bifurcation lesions (0.94 ± 0.3 in crush vs. 0.90 ± 0.08 in provisional group, P = 0.028) [46]. These results suggest that SB FFR can be helpful to assess the procedural success after SB stenting.…”
Section: Ffr After Sb Stentingmentioning
confidence: 84%
“…We identified 14 published RCTs (3,107 patients) that met our inclusion criteria (Figure 1), with a mean follow-up time of 25.6 months [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. A total of 1,522 patients were treated with a SS strategy, and 1,585 patients were managed with a DS approach (ITT).…”
Section: Study Selectionmentioning
confidence: 99%
“…However, randomized control trials (RCTs) have been too underpowered to detect differences of ST rates between SS versus DS group [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], although there has been a trend in a reduction of ST with a SS strategy [11,13,14,16,18]. In addition, owing to variable follow-up durations across studies (6-60 months), evaluation of the true rate of late, very late or overall ST is difficult [28][29][30][31][32].…”
mentioning
confidence: 99%
“…既往研究显示 [17] ,支架术后 FFR 所测结果是心血管事件的独立预测因子,FFR>0.9 的患者,支架术后 心血管事件发生率明显降低。FFR 能够对复杂的分叉病变双支架植入术提供有价值的参考信息。Lee 等 [18] 对分叉病变采取 Crush 术式后,对主支和边支行对吻性球囊扩张,术前术后均行 FFR 检测,结果发现对吻 性球囊扩张可明显提升边支的 FFR 值。另一项研究表明 [19] ,对于真性分叉病变,双对吻 Crush 支架术较必 要时边支支架术能取得更好的 FFR 值。这些研究结果提示,边支支架术后的 FFR 测量有助于评估支架植入 后的效果,然而需要注意的是,较高的 FFR 值并不总是意味着复杂病变后有更好的预后,FFR 在预测边支 支架术后的远期疗效方面尚有局限性。 …”
Section: 边支支架植入后的 Ffr 测量unclassified